Islamic Bond Announcement: Is There Any Effect on Returns? - Fauzi, Fitriya; Foo, D.; Basyith, A. (Sage Publications India Pty Ltd, 2017)
© 2017, © 2017 International Management Institute, New Delhi. This article investigates the effect of Islamic debt announcement on stock returns. Using data from 80 Malaysian firms and 20 Indonesian firms, which span from 2000 to 2009, an event study analysis is employed in this study; hence, the data of the daily closing stock prices for 2 years prior and 1 year after the announcement date are required in order to calculate the abnormal return using the abnormal return benchmark (mean adjusted return, market adjusted return and market model return). The findings for the event study analysis, using three benchmarks, reveal that there is a negative and significant impact for both average abnormal returns (AAR) and cumulative average abnormal returns (CAAR) for Malaysia. In contrast to the findings for Malaysia, the impact of Islamic debt announcement, using three benchmarks, is positive and significant for both AAR and CAAR for Indonesia. The unit root test result for Malaysia indicates that the market is efficient in the context of weak form efficiency, which suggests that the price movements are unpredictable. In contrast to Malaysia, the unit root test result for Indonesia indicates that the market is inefficient in the context of weak form efficiency, which suggests that the price movements are predictable.